SPORTS FACILITIES AND EQUIPMENT AT BRATISLAVA GRAMMAR SCHOOLS IN SLOVAKIA (Fiep Bulletin - online, 2011)
In our study we deal with the issue of physical education and sport facilities at grammar schools in Bratislava. The aim of the study was to update and extend knowledge of spatial - material equipment of physical education and sports at schools in Bratislava and to compare the results with the results from the year 1990 and to evaluate opinions of teachers of physical education and sports about these issues.
Keywords: physical education and sports; physical education and sports facilities; material equipment; spatial equipment